A large-scale screening identified in USH2A gene the P3272L founder pathogenic variant explaining familial Usher syndrome in Sardinia, Italy - Serra, Rita; Rallo, Vincenzo; Steri, Maristella; Olla, Stefania; Piras, Maria Grazia; Marongiu, Michele; Gorospe, Myriam; Schlessinger, David; Pinna, Antonio; Fiorillo, Edoardo; Cucca, Francesco; Angius, Andrea (BMC ophthalmology, 2024)
Background Usher syndrome (USH) encompasses a group of disorders characterized by congenital sensorineural hearing loss (SNHL) and retinitis pigmentosa (RP). We described the clinical findings, natural history, and molecular analyses of USH patients identified during a large-scale screening to identify quantitative traits related to ocular disorders in the SardiNIA project cohort. Methods We identified 3 USH-affected families out of a cohort of 6,148 healthy subjects. 9 subjects presented a pathological phenotype, with SNHL and RP. All patients and their family members underwent a complete ophthalmic examination including best-corrected visual acuity, slit-lamp biomicroscopy, fundoscopy, fundus autofluorescence, spectral-domain optical coherence tomography, and electrophysiological testing. Audiological evaluation was performed with a clinical audiometer. Genotyping was performed using several arrays integrated with whole genome sequence data providing approximately 22 million markers equally distributed for each subject analyzed. Molecular diagnostics focused on analysis of the following candidate genes: MYO7A, USH1C, CDH23, PCDH15, USH1G, CIB2, USH2A, GPR98, DFNB31, CLRN1, and PDZD7 . Results A single missense causal variant in USH2A gene was identified in homozygous status in all patients and in heterozygous status in unaffected parents. The presence of multiple homozygous patients with the same phenotypic severity of the syndromic form suggests that the Sardinian USH phenotype is the result of a founder effect on a specific pathogenic variant related haplotype. The frequency of heterozygotes in general Sardinian population is 1.89. Additionally, to provide new insights into the structure of usherin and the pathological mechanisms caused by small pathogenic in-frame variants, like p.Pro3272Leu, molecular dynamics simulations of native and mutant protein–protein and protein–ligand complexes were performed that predicted a destabilization of the protein with a decrease in the free energy change. Conclusions Our results suggest that our approach is effective for the genetic diagnosis of USH. Based on the heterozygous frequency, targeted screening of this variant in the general population and in families at risk or with familial USH can be suggested. This can lead to more accurate molecular diagnosis, better genetic counseling, and improved molecular epidemiology data that are critical for future intervention plans. Trial registration We did not perform any health-related interventions for the participants.